Synthesis of carbon-11 radiolabelled transition metal complexes using 11C-dithiocarbamates. Issue 13 (16th March 2022) - Cesarec, Sara; Edgar, Fraser; Lai, Titan; Plisson, Christophe; White, Andrew J. P.; Miller, Philip W.
Abstract : Fast and efficient radiolabelling using 11 C-dithiocarbamate ligands to generate a range of novel 11 C-labelled transition metal complexes in high radiochemical yields. Abstract : A novel radiolabelling method exploiting 11 C-dithiocarbamate ligands has been used to generate 11 C-labelled Au(i ), Au(iii ), Pd(ii ) and Pt(ii ) complexes in high radiochemical yields (71–99%). Labelled complexes were prepared in a rapid one-pot procedure via the substitution reaction of 11 C-dithiocarbamate ligands with appropriate transition metal chloride precursors.